Морфологические особенности крота обыкновенного (Talpa europaea L.) из западных областей Украины - Сенык, А.Ф. (Вестник зоологии, 1974)
The mole from the Ukrainian Carpathians is less in size than that from the plains of the western regions of the Ukrainian SSR and nominal subspecies, but it is bigger than the south-european mole-Talpa coeca Savi. It ought to be considered as the smallest of Talpa europaea subspecies-T. europaea panicici Martino, 1930, dia- gnosted by S. U. Stroganov (1948) by the materials from Yugoslavia.